INTERNATIONAL TOURISTS’ EXPENDITURES IN THAILAND: A MODELLING OF THE ARFIMA-FIGARCH APPROACH - KANCHANA CHOKETHAWORN; AREE WIBOONPONSE; SONGSAK SRIBOONCHITTA; JITTAPORN SRIBOONJIT; CHUKIAT CHAIBOONSRI; PRASERT CHAITIP (Annals of the University of Petrosani: Economics, 2010)
Forecasting is an essential analytical tool for tourism policy andplanning. This paper focuses on forecasting methods based on ARFIMA(p,d,q)-FIGARCH(p,d,q). Secondary data was used to produce forecasts of international tourists’expenditures in Thailand for the period 2009-2010. The results of this research for this periodconfirms that the best forecasting method based on ARFIMA(p,d,q)-FIGARCH(p,d,q) method isthe ARFIMA(1,-0.672,1)-FIGARCH(1,-0.180,1) method. Furthermore, this method predicts theexpenditures of tourists in Thailand for the period of 2009-2010 will be constant or decline. Ifthese results can be generalized for future years, then it suggests that both the Thailandgovernment sector and also the private tourism industry sector of Thailand need to develop thetourism market of Thailand immediately and also develop tourism products in Thailand.